Beginning iOS 3D Unreal Games Development - Chin, Robert; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
The Unreal UDK features Epic's award-winning Unreal Engine 3, used to create bestselling games such as Infinity Blade for iOS, and popular console games like Borderlands and Bioshock. Now, you can build your own Unreal game for the iOS platform. Beginning iOS 3D Unreal Games Development covers using the Unreal UDK game creation system to create 3D games for the iOS platform, which includes the iPhone, iPod touch and iPad.  Specifically, this book covers: UnrealScript programming language, going beyond the limitations of the visual Kismet scripting language The Unreal UDK code framework, basic UDK tools and other UDK items needed to build a game Various author-created game frameworks are presented and are used to illustrate the UnrealScript programming language and user input methods specific to the iOS mobile platform.
Keywords: Apple computer; Application software; Apple and iOS; Computer Applications